TOXICOLOGICAL AND HISTOPATHOLOGICAL IMPACT OF INSECTICIDE ACETAMIPRID AND AGRICULTURAL FERTILIZER ACTIVEG ON EARTHWORM (Aporrectodea giardi) (Applied Biological Research, 2023)
Earthworms provide important information about the environmental risks  so serve as useful biological indicators of soil contamination. The present  study was aimed to assess the impact of insecticide ‘Acetamiprid’ and  fertilizer ‘Activeg’ (widely used fertilizer in Algeria), on earthworm  Aporrectodea giardi. The earthworms were subjected to four different  doses of Acetamiprid viz., 25, 50, 100 and 200 mg 500 mg-1soil for four  periods viz., 24, 48, 72 and 96 h. The toxicological and histopathological  evaluations were also conducted. Based on physiochemical analysis, soil  proved to be a convenient environment for earthworms. The soil was  sandy loam in texture, neutral in pH and rich in organic matter (8.93%)  with a field capacity of 19.37. Earthworm mortality showed increase with increase in Acetamiprid dose with LD50 value varying from 89.03 to 240.23  mg kg-1. Histological studies revealed marked alterations in epidermal and  intestinal cells. Earthworm exposed to fertilizer Activeg showed neither earthworm mortality nor any toxicological effects on their tissue structure.  The study confirmed the deleterious effect of Actamiprid on A. giardi, so it  should be used with prudence in order to save the soil animal fauna.
Keywords: Acetamiprid; Activeg; Aporrectodea giardi; earthworm; histopathology; LD50; mortality